2019
DOI: 10.1037/cdp0000267
|View full text |Cite
|
Sign up to set email alerts
|

Blacks’ perception of a Biracial’s ingroup membership shapes attributions to discrimination following social rejection.

Abstract: Objectives: The present research examined if Blacks differ in how they categorize Blacks, Whites, and Black–White Biracials (Biracials, hereafter) as ingroup members and whether those categorizations predict the degree to which they attribute rejection feedback to discrimination. Methods: In Study 1 (N = 115), Black participants received rejection feedback from a Black, White, or Biracial online partner and then indicated the extent to which they perceived their partner as part of their racial ingroup and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 62 publications
2
15
1
Order By: Relevance
“…Linked fate indicates that Black people perceive their progress signifies progress for Biracial people and vice versa (Ho et al, 2017). While previous research suggests Black people perceive Biracial-identified people as being just as much an ingroup member as Black-identified people (Smith & Wout, 2019), this relationship differs when assessed using linked fate. We find Black people indirectly ascribe less empathy toward Biracial targets who are either Biracial-or White-identified compared to those who are Black-identified, as they perceive less linked fate with non-Black-identified targets.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Linked fate indicates that Black people perceive their progress signifies progress for Biracial people and vice versa (Ho et al, 2017). While previous research suggests Black people perceive Biracial-identified people as being just as much an ingroup member as Black-identified people (Smith & Wout, 2019), this relationship differs when assessed using linked fate. We find Black people indirectly ascribe less empathy toward Biracial targets who are either Biracial-or White-identified compared to those who are Black-identified, as they perceive less linked fate with non-Black-identified targets.…”
Section: Discussionmentioning
confidence: 94%
“…Generally, rates of rejection of Black/White Biracial people from the Black community are low (Franco et al, 2019; Franco & Holmes, 2016) but are more likely among Black people who endorse a nationalist racial ideology (Franco et al, 2019). Thus, Biracial people sometimes experience “conditional acceptance” into the Black community, wherein their status as ingroup members may be partially revoked, particularly when they identify as White or Biracial over Black (Harris & Khanna, 2010; Rockquemore & Brunsma, 2001; Smith & Wout, 2019; Thorton, 2009). While the racial classification literature suggests Black people see Biracial people as racial ingroup members, research with Biracial participants complicates these findings.…”
Section: Status Of Black/white Biracial People In the Black Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although individuals with low public regard tend to perceive more racial discrimination in society, research has shown that low public regard can protect Black people from the negative psychological consequences of discrimination (Sellers et al, 2006; Sellers & Shelton, 2003). Individuals with low public regard likely anticipate negative treatment by racial outgroup members and minimize psychological distress by attributing this mistreatment to racial discrimination rather than personal shortcomings (Smith & Wout, 2019; Wout, Murphy, & Steele, 2010). The meaning‐making process among Black female students in this study may have led them to recognize that the AWA is a culturally oppressive insult that is rooted within a system of White supremacy designed to normalize White traits and perpetuate negative stereotypes prescribed to non‐White populations (Durkee et al, 2019; Fanon, 1952).…”
Section: Discussionmentioning
confidence: 99%
“…Cultural invalidations may target people’s sense of belonging to the social groups they identify with, prompting changes in their identity beliefs. For example, Black multiracial people are perceived more negatively by monoracial Black people when they display identity markers of only one of their cultural backgrounds and are more likely to report experiencing racial homelessness (i.e., feelings of rejection from one’s racial group; Franco & Franco, 2016; Smith & Wout, 2019). Findings from Cheryan and Monin (2005) indicate that Asian American students who experience identity threats attacking their American identity become motivated to demonstrate more American behaviors and characteristics, such as listening to American music, playing American sports, and having American friends.…”
Section: Racial Identity Developmentmentioning
confidence: 99%